Treatment of Acute Antibody-Mediated Renal Allograft Rejection With Cyclophosphamide. Issue 10 (October 2017) - Waiser, Johannes; Duerr, Michael; Budde, Klemens; Rudolph, Birgit; Wu, Kaiyin; Bachmann, Friederike; Halleck, Fabian; Schönemann, Constanze; Lachmann, Nils
Abstract : Background: Antibody-mediated rejection (AMR) is a major risk for renal allograft survival. Throughout decades, cyclophosphamide treatment has been proven to be effective in patients with antibody-associated autoimmune diseases. We investigated whether cyclophosphamide combined with plasmapheresis and intravenous immunoglobulins is an option for patients with AMR. Methods: Between March 2013 and November 2015, we initiated treatment of 13 consecutive patients with biopsy-proven acute AMR with intravenous cyclophosphamide pulses (15 mg/kg adapted to age and renal function) at 3-week intervals, PPH (6×), and high-dose intravenous immunoglobulin (1.5 g/kg). Treatment was completed after 6 cyclophosphamide pulses or in case of return to baseline serum creatinine together with reduction of donor-specific HLA antibodies (DSA) below 500 mean fluorescence intensity. Results: Eleven of 13 patients completed treatment. Median follow-up was 18 (12-44) months. At the end of follow-up, graft survival was 77% (10/13). The 3 graft losses were caused at least in part by nonadherence and premature termination of treatment. Serum creatinine increased from 1.7±0.4 mg/dL at 3 months before diagnosis to 3.7±2.4 mg/dL at diagnosis ( P = 0.01), and decreased to 2.1 ± 0.7 mg/dL at 3 months after diagnosis ( P = 0.01). In 7 (64%) of 11 patients, who completed treatment, DSA decreased, in 4 (36%) of 11 DSA were below 500 mean fluorescence intensity after treatment. Dose reductions had to be performed in 3 of 13 patients for leukopenia. We observed 14 hospitalizations in 9 of 13 patients. Conclusions: To our knowledge, this is the first systematic report on cyclophosphamide-based treatment of acute AMR based on modern diagnostics. Treatment was effective and relatively safe. Future studies will show, whether cyclophosphamide proves to be a valuable alternative for the treatment of AMR. Abstract : The authors first report on 13 kidney transplant recipients with antibody-mediated rejection treated with cyclophosphamide, plasma exchange and IVIg with a mean follow up of 18 months with a decrease in serum creatinine, in DSA MFI and a small incidence of neutropenia.